Analysis and optimization of meshing characteristics of power-split hub reducers - WANG Zhao; LÜ Zhenyu; LIU Keke; ZHANG Wenxia; ZHOU Guocheng; MA Tianqi (Jixie chuandong)
ObjectiveAiming at the meshing characteristics of the hub reducer, the transmission system analysis software KISSsoft is used to analyze it, and the meshing quality is improved through optimization methods.MethodsFirstly, a meshing analysis model of the hub reducer was established by using KISSsoft, and the meshing parameters such as contact performance, tooth root stress, and mesh stiffness of the reducer under rated conditions were deeply analyzed. Then, based on the previous analysis, by optimizing the pressure angles of each stage of the reducer and micro-profile modification of the hub reducer, the influence of pressure angle optimization on the maximum contact stress and meshing stiffness was analyzed, and the influence of tooth profile modification on the meshing characteristic parameters of the hub reducer was studied.ResultsThe results show that there is an off-load phenomenon in the tooth profile direction of the hub reducer under rated conditions, and the maximum contact stress of some meshing pairs is on the high side. Through means such as optimizing the pressure angle and tooth profile modification, the meshing characteristics of the hub reducer can be optimized, the stress peak can be eliminated, and the meshing quality can be improved.